Perceived and Objective Quality of Life Among Pregnant Women: Mixed-Methods Research on Chronic Energy Deficiency - Fitri Apriyanti; Diah Wulandari; M. Nizar Syarif Hamidi (Postgraduate, University of Mataram, 2025)
Chronic Energy Deficiency (CED) in pregnant women is a substantial public health issue in Indonesia. This research examines the divergence between objective and subjective quality of life in pregnant women with CED in Kampar District, Riau Province. A sequential explanatory design with mixed methodologies was used. The quantitative phase included 150 pregnant women with chronic energy deficiency (mid-upper arm circumference <23.5 cm) from 10 community health centers (out of 31 in Kampar District), selected using a strategy that guarantees a blend of urban and rural regions. Evaluations included WHOQOL-BREF, anthropometric assessments, and clinical exams. The qualitative phase included comprehensive interviews and focus group discussions with 30 intentionally chosen individuals. Data integration was executed by joint display analysis. Quantitative results indicated poor objective quality of life scores: physical domain: 54.3±12.7; psychological: 58.6±11.4; social: 64.2±13.8; environmental: 52.1±10.9. Nonetheless, 73% of interviewees regarded their quality of life as